mbtD and celA1 association with ethambutol resistance in Mycobacterium tuberculosis: A multiomics analysis - Wu, Zhuhua; Tan, Qiuchan; Zhang, Chenchen; Zhao, Yuchuan; Liao, Qinghua; Yu, Meiling; Xu, Liuyue; Wang, Jiawen; Liang, Hongdi; Li, Haicheng; Chen, Liang; Chen, Xunxun; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Ethambutol (EMB) is a first-line antituberculosis drug currently being used clinically to treat tuberculosis. Mutations in the embCAB operon are responsible for EMB resistance. However, the discrepancies between genotypic and phenotypic EMB resistance have attracted much attention. We induced EMB resistance in Mycobacterium tuberculosis in vitro and used an integrated genome–methylome–transcriptome–proteome approach to study the microevolutionary mechanism of EMB resistance. We identified 509 aberrantly methylated genes (313 hypermethylated genes and 196 hypomethylated genes). Moreover, some hypermethylated and hypomethylated genes were identified using RNA-seq profiling. Correlation analysis revealed that the differential methylation of genes was negatively correlated with transcription levels in EMB-resistant strains. Additionally, two hypermethylated candidate genes (mbtD and celA1) were screened by iTRAQ-based quantitative proteomics analysis, verified by qPCR, and corresponded with DNA methylation differences. This is the first report that identifies EMB resistance-related genes in laboratory-induced mono-EMB-resistant M. tuberculosis using multi-omics profiling. Understanding the epigenetic features associated with EMB resistance may provide new insights into the underlying molecular mechanisms.